Analisis Pengendalian Persediaan Bahan Baku Tangki BBM dengan Metode EOQ dan ROP (Studi Kasus: PT. Meco Inoxprima) - Muhammad Burhan Jamaluddin; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the control of raw material inventory in the fuel tank manufacturing process at PT Meco Inoxprima to improve production flow and cost efficiency. The company’s main problem is delays in the procurement of imported raw materials, which disrupt production schedules and increase operating costs. The methods used are EOQ, Safety Stock, and ROP, utilizing historical data from 2025–2026. The results indicate optimal order quantities of 435 sheets (aluminum alloy), 334 sheets (stainless steel), and 281 sheets (mild steel). Safety stock is set at 102, 43, and 36 sheets for each material, respectively. The ROP values are 480, 197, and 92 sheets. Total inventory costs decrease from Rp. 136,250,000 to Rp. 107,890,000 per year, resulting in savings of Rp. 28,360,000 (20.82%). The application of the EOQ, Safety Stock, and ROP methods has proven effective in improving operational cost efficiency and ensuring smooth production.